Measuring Urban Heat Islands in Metropolitan City, Pokhara, Using Remote Sensing - Jamarkattel, Utsav; Sherchan, Bikash; K C, Niraj (Journal of Engineering and Sciences, 2024)
This study investigates the Urban Heat Island (UHI) effect in Pokhara Metropolitan City using remote sensing and geographic information systems (GIS). The primary objective is to analyze temporal and spatial variations in UHIs, with secondary objectives including evaluating spatial patterns of Land Surface Temperature (LST) and assessing changes in UHI intensity over time. Landsat 8 imagery from 2013 to 2022 was processed using Google Earth Engine (GEE) to derive LST maps. Data preprocessing involved band selection, cloud masking, and spatial filtering to enhance data quality. Urban and suburban areas were delineated using shapefiles, facilitating the calculation of Surface Urban Heat Island (SUHI) intensity across the city. Results indicate pronounced spatial disparities in LST, with urban areas consistently registering higher temperatures than suburban counterparts. The average LST in urban areas peaked at 39.13°C, compared to 34.43°C in suburban areas. Temporal analysis reveals a steady rise in both LST and SUHI intensity over the study period, with SUHI values increasing from 2.99 in 2013 to 5.85 in 2022, highlighting the escalating impact of urbanization on local climate dynamics. This research contributes crucial insights into the urban thermal environment of Pokhara Metropolitan City, essential for informing sustainable urban planning and climate resilience strategies in rapidly developing regions.Keywords: Sub-urban; Urban; Island; Hot spots; Land Surface Temperature; Urban Heat Intensity